Negative electrode sheet, secondary battery and electric device
By setting a layer of negative electrode active material with control characteristics in the negative electrode sheet of the secondary battery, the problem of limited performance of the existing secondary battery is solved, and a higher cycle capacity retention rate and dynamic performance balance is achieved.
Patent Information
- Application Number
- CN202211505013.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-11-29
AI Technical Summary
The selection of negative active materials for existing secondary batteries is limited, resulting in reduced charge and discharge efficiency, poor cycle performance, and lower capacity retention.
By providing a negative electrode active material layer containing negative electrode active material particles in the negative electrode sheet, the ID/IG values and ratios of the surface layer and the substrate layer are controlled to form a dense and stable SEI film to improve the lithium ion embedding/detachment efficiency.
The first Coulomb efficiency and cycle capacity retention of the secondary battery are improved, and the balance between kinetic performance is maintained.
Smart Images

Figure CN115911261B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a negative electrode plate, a secondary battery and an electrical device. Background Art
[0002] In recent years, as secondary batteries represented by lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, people have also put forward higher requirements on the energy density, safety, cycle performance, etc. of secondary batteries.
[0003] In the prior art, the selection of negative electrode active materials in secondary batteries is relatively limited, which will lead to different degrees of limitations in the performance of secondary batteries, such as reduced charging and discharging efficiency, poor cycle performance, low capacity retention rate, etc. Therefore, the existing negative electrode active materials and negative electrode sheets still need to be improved. Summary of the invention
[0004] The present application provides a negative electrode plate, a secondary battery and an electrical device, aiming to improve the cycle capacity retention rate and balanced kinetic performance of the secondary battery.
[0005] The first aspect of the present application provides a negative electrode sheet, comprising:
[0006] Anode current collector;
[0007] A negative electrode active material layer containing negative electrode active material particles is disposed on at least one side of the negative electrode current collector, the negative electrode active material layer includes a surface layer with an ID1 / IG1 value of A and a matrix layer with an ID2 / IG2 value of B, the matrix layer is located between the negative electrode current collector and the surface layer, wherein 0.55≤A≤0.78, 0.78≤B≤0.96, and 0.60≤A / B<1.0. In the above relationship, ID1 is the Raman spectrum of the negative electrode active material in the surface layer at a Raman shift of 1328-1359cm -1 IG1 is the peak intensity of the scattering peak at the surface layer, and IG2 is the Raman spectrum of the negative electrode active material at the Raman shift of 1578-1585 cm -1 ID2 is the peak intensity of the scattering peak at the Raman shift of 1328-1359 cm -1 IG2 is the peak intensity of the scattering peak at 1578-1585 cm-1, and IG2 is the Raman spectrum of the negative electrode active material in the matrix layer at a Raman shift of 1578-1585 cm-1. -1 The peak intensity of the scattering peak at .
[0008] Through research, it is found that the negative electrode active material layer formed by the negative electrode active material particles has a surface layer and a matrix layer that conform to the above relationship. By controlling the ID / IG value A of the surface layer, the ID / IG value B of the matrix layer and the ratio A / B within the above ranges, on the one hand, the surface defect degree of the negative electrode active material layer can be controlled, which is conducive to the formation of a dense and stable SEI film on the surface of the negative electrode active material layer. On the other hand, the negative electrode active material layer can have improved lithium ion insertion / extraction efficiency, thereby improving the first coulombic efficiency and cycle capacity retention rate of the secondary battery, and maintaining a balance between kinetic performance.
[0009] In any embodiment of the first aspect of the present application, the negative electrode active material layer satisfies: 0.70≤A / B≤0.96.
[0010] In any embodiment of the first aspect of the present application, the negative electrode active material layer satisfies: 0.75≤A / B≤0.85
[0011] In any embodiment of the first aspect of the present application, the thickness of the surface layer is 5 μm to 20 μm. The thickness of the surface layer within the above range can take into account the preparation process cost and the formation of the SEI film, and further improve the initial coulombic efficiency and cycle capacity retention rate of the secondary battery.
[0012] In any embodiment of the first aspect of the present application, the thickness of the negative electrode active material layer is 30 μm to 160 μm. The thickness of the negative electrode active material layer is too small, for example, less than 30 μm. On the one hand, the thin negative electrode active material layer is easily infiltrated by the electrolyte, and the lithium ions are easier to be deintercalated. The surface layer and the matrix layer with different ID / IG values are arranged on the negative electrode active material layer, and the ratio of the ID / IG of the two is controlled, which has a limited degree of improvement in the performance of the secondary battery. On the other hand, the negative electrode active material layer is too thin, which reduces the proportion of the negative electrode active material layer in the negative electrode sheet, thereby reducing the energy density of the secondary battery. The negative electrode active material layer is too thick, for example, greater than 160 μm, and it is difficult for the electrolyte to infiltrate the negative electrode active material in the middle, and the side reaction products caused by polarization accumulate, and the cycle performance and kinetic performance of the secondary battery are deteriorated.
[0013] In any embodiment of the first aspect of the present application, the negative electrode plate satisfies at least one of the following conditions:
[0014] (1) The maximum particle size of the negative electrode active material particles is ≤55 μm;
[0015] (2) The Dv50 of the negative electrode active material particles is 5 μm to 15 μm;
[0016] (3) The ratio Dv90 / Dv10 of the negative electrode active material particles is 1.2 to 3.2.
[0017] In any embodiment of the first aspect of the present application, the negative electrode active material comprises at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, and carbon-silicon composites.
[0018] In any embodiment of the first aspect of the present application, the negative electrode plate further comprises a primer layer disposed between the negative electrode current collector and the substrate layer, wherein the primer layer comprises a conductive agent. By providing a primer layer containing a conductive agent, the bonding force between the negative electrode active material layer and the current collector can be improved, and the negative electrode plate can be prevented from falling off from the current collector due to repeated expansion and contraction during the cycle, thereby improving the shape stability of the secondary battery during the cycle, and improving the cyclability and rate capability of the secondary battery.
[0019] In any embodiment of the first aspect of the present application, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, carbon fibers and graphene.
[0020] In any embodiment of the first aspect of the present application, the thickness of the primer layer is 0.01 μm to 2 μm. If the primer layer is too thin, for example, less than 0.01 μm, coating control is difficult, and the primer layer has an insignificant effect of improving the bonding force between the current collector and the negative electrode active material layer; if the primer layer is too thick, for example, greater than 2 μm, the primer layer does not provide capacity, and therefore, the energy density of the secondary battery is reduced.
[0021] A second aspect of the present application provides a secondary battery, comprising the negative electrode plate of the first aspect.
[0022] A third aspect of the present application provides an electrical device, comprising the secondary battery of the second aspect.
[0023] According to the negative electrode sheet provided in the embodiment of the present application, the value A of ID / IG of the surface layer, the value B of ID / IG of the substrate layer and the ratio A / B are controlled at 0.55≤A≤0.78, 0.78≤B≤0.96, and 0.60≤A / B<1.0. On the one hand, the surface defect degree of the negative active material layer in the negative electrode sheet can be controlled, which is conducive to forming a dense and stable SEI film on the surface of the negative electrode sheet. On the other hand, the lithium ion insertion / extraction efficiency can be improved on the surface of the negative electrode sheet, which can make the stability of the formed SEI film conducive to obtaining a better balance between the first coulomb efficiency and the cycle capacity retention rate of the secondary battery.
[0024] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a schematic diagram of an embodiment of a negative electrode sheet in a secondary battery of the present application;
[0026] Figure 2 This is a Raman spectrum of a matrix layer in a negative electrode active material layer in a negative electrode sheet of an embodiment of the present application;
[0027] Figure 3 is a schematic diagram of another embodiment of the negative electrode sheet in the secondary battery of the present application;
[0028] Figure 4 is a schematic diagram of an implementation of a secondary battery of the present application;
[0029] Figure 5 yes Figure 4 An exploded view of an embodiment of a secondary battery of the present application is shown;
[0030] Figure 6 Schematic diagram of an electrical device using the secondary battery of the present application as a power source.
[0031] Description of reference numerals:
[0032] 10 negative electrode plate; 11 negative electrode current collector; 12 bottom coating layer; 13 negative electrode active material layer; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0033] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0035] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0036] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0037] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0038] In the description of the embodiments of the present application, unless otherwise specified, "above" and "below" are inclusive of the number, and "multiple" and "a plurality" in "one or more" and "one or more" mean more than two (or more).
[0039] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0040] The grouping of alternative elements or embodiments disclosed herein should not be construed as limiting. Each group member may be adopted and claimed individually, or with other members of the group or other elements found herein in any combination. It is anticipated that one or more members of a group may be included in or deleted from the group for convenience and / or patentability reasons. When any such inclusion or deletion occurs, the specification is considered herein to contain the modified group, thus satisfying the written description of all Markush groups used in the claims.
[0041] Without departing from the scope of protection of the present application, various modifications and changes can be made in the present application, which will be apparent to those skilled in the art. Therefore, the present application is intended to cover modifications and changes of the present application that fall within the scope of the corresponding claims (scopes for protection) and their equivalents. It should be noted that the implementation methods provided in the embodiments of the present application can be combined with each other without contradiction.
[0042] Before explaining the scope of protection provided by the embodiments of the present application, in order to facilitate the understanding of the embodiments of the present application, the present application first specifically describes the problems existing in the related technology.
[0043] With the application of secondary batteries represented by lithium-ion batteries in various industries, the requirements for the performance of negative electrode plates are becoming increasingly stringent. Conventional negative electrode plates can no longer meet the requirements of cycle performance and kinetic performance.
[0044] For example, when a lithium-ion battery is charged for the first time, the solvent and lithium salt around the negative electrode plate react in a complex manner on the surface of the negative electrode active material layer containing, for example, graphite particles, to form a deposited solid electrolyte interface film (hereinafter referred to as SEI film), the main components of which include alkyl lithium, lithium carbonate, and lithium fluoride, etc. Generally speaking, since the SEI film is a passivation layer, it can withstand the action of the electrolyte, isolate the negative electrode active material particles from the electrolyte, and prevent the electrolyte from damaging the structure of the negative electrode active material particles.
[0045] The applicant has found that the formation of the SEI film has an important influence on the performance of secondary batteries. On the one hand, a dense and stable SEI film can reliably protect the negative electrode active material from the erosion of the electrolyte, ensure that the negative electrode active material maintains structural stability during the charging and discharging process of the lithium-ion battery, and prevent its electrochemical performance from deteriorating, thereby improving the cycle performance of the lithium-ion battery; on the other hand, the formation of the SEI film will consume lithium ions, increase the irreversible capacity during the first charge and discharge, and reduce the first coulomb efficiency of the lithium-ion battery. Further research has found that the formation of the SEI film is related to the surface defects (also known as disorder) of the negative electrode active material. A higher surface defect degree of the negative electrode active material will increase the formation of the SEI film, but it will also consume more lithium ions, which will have a certain impact on the battery's cycle performance and the battery's first coulomb efficiency.
[0046] In view of this, the present application provides a negative electrode plate, a secondary battery and an electrical device. The negative electrode plate controls the surface defect degree of the negative electrode active material layer on the surface, controls the formation and stability of the SEI film, so that the secondary battery having the above-mentioned negative electrode plate has better cycle capacity retention rate and dynamic performance.
[0047] In the present application, a secondary battery includes any device that undergoes an electrochemical reaction to convert chemical energy into electrical energy. Secondary batteries include common secondary batteries in the art such as lithium-ion batteries and sodium-ion batteries, and a specific example thereof is a lithium secondary battery, which may include a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0048] Negative electrode
[0049] The embodiment of the first aspect of the present application provides a negative electrode sheet, including a negative electrode current collector; a negative electrode active material layer containing negative electrode active material particles disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer includes:
[0050] The ID1 / IG1 value is the surface layer of A, where 0.55≤A≤0.78, and ID1 is the Raman shift of the negative electrode active material in the surface layer at 1328-1359 cm -1 IG1 is the peak intensity of the scattering peak at the surface layer, and IG2 is the Raman spectrum of the negative electrode active material at the Raman shift of 1578-1585 cm -1 The peak intensity of the scattering peak at ;
[0051] ID2 / IG2 value is B for the matrix layer, which is located between the negative electrode current collector and the surface layer, where 0.78≤B≤0.96, and ID2 is the Raman spectrum of the negative electrode active material in the matrix layer at a Raman shift of 1328-1359cm -1IG2 is the peak intensity of the scattering peak at 1578-1585 cm-1, and IG2 is the Raman spectrum of the negative electrode active material in the matrix layer at a Raman shift of 1578-1585 cm-1. -1 The peak intensity of the scattering peak at, the negative electrode active material layer satisfies, 0.60≤A / B<1.0.
[0052] According to the embodiment of the present application, the negative electrode active material layer satisfies: 0.60≤A / B<1.0. For example, the ID1 / IG1 value of the surface layer and the ID2 / IG2 value of the substrate layer can be 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.96 or other values within the range of any of the above values. Since the negative electrode active material layer needs to make the SEI film stable and maintain the balance of kinetic performance, A / B is usually not set to be greater than or equal to 1.
[0053] In some embodiments of the present application, the negative electrode active material layer satisfies: 0.70≤A / B≤0.96. When the ratio A / B is within the above range, a better balance can be achieved between the stability of the formed SEI film, the first coulombic efficiency of the secondary battery, and the cycle capacity retention rate.
[0054] In some embodiments of the present application, the negative electrode active material layer satisfies: 0.75≤A / B≤0.85. When the ratio A / B is within the above range, the stability of the formed SEI film, the first coulombic efficiency of the secondary battery, and the cycle capacity retention rate can be further optimized.
[0055] In some embodiments, the surface layer has an ID1 / IG1 value of A, wherein the value of A is 0.55 to 0.78; it can be 0.55, 0.56, 0.58, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78 or other values within the range of any of the above values. Controlling the surface layer with an ID1 / IG1 value of A within the above range not only controls the defectivity of the surface layer, which is beneficial to the lithium ion insertion / extraction efficiency, but also facilitates the formation of a dense SEI film.
[0056] In some embodiments, the ID2 / IG2 value is B, and the matrix layer is located between the negative electrode current collector and the surface layer, wherein the value of B is 0.78 to 0.96; it can be 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91,
[0057] 0.92, 0.93, 0.94, 0.96 or other values within the range of any of the above values. Controlling the ID2 / IG2 value of the matrix layer to be B is beneficial to the capacity of the negative electrode active material and the capacity retention rate during the cycle process, and can also reduce battery polarization, reduce the irreversible capacity of the battery, and effectively control lithium plating.
[0058] Figure 1 1 is a schematic diagram of an embodiment of a negative electrode sheet in a primary / secondary battery of the present application. The exemplary negative electrode sheet 10 includes a negative electrode current collector 11 and a negative electrode active material layer 13 located on the surface of the negative electrode current collector 11 .
[0059] In some embodiments, the negative electrode sheet may be provided with a negative electrode active material layer on one surface of the negative electrode current collector, or may be provided with negative electrode active material layers on both surfaces of the negative electrode current collector, which is not particularly limited in the embodiments of the present application.
[0060] According to an embodiment of the present application, the negative electrode current collector may be a metal foil or a porous metal plate, such as a foil or a porous plate of a metal such as copper, nickel, titanium, iron, or an alloy thereof.
[0061] In some embodiments of the present application, the negative electrode current collector is copper foil. In some embodiments of the present application, the thickness of the negative electrode current collector may be 4 μm to 12 μm.
[0062] It should be noted that the ID1 value and IG1 value of the surface layer and the ID2 value and IG2 value of the matrix layer can be measured by the Raman spectrum of the negative electrode active material using instruments and methods known in the art. For example, the negative electrode active material layer is cut into a cross section by an ion polishing method, and then the cross section is placed on a Raman spectrum test bench, and the Raman spectrum of the negative electrode active material layer is tested after focusing. For example, a Raman spectrometer is used.
[0063] The ID1 value and IG1 value of the surface layer and the ID2 value and IG2 value of the substrate layer in the embodiment of the present application can be measured by LabRAM HR Evolution laser micro-Raman spectrometer. A solid laser with a wavelength of 523nm can be used as a light source, with a beam diameter of 1.2μm and a power of 1mW; the measurement mode is macro Raman; and a CCD detector is used.
[0064] Figure 2 The Raman spectrum of the substrate layer is shown, wherein the horizontal axis is the Raman shift and the vertical axis is the relative intensity. The ID peak and IG peak are marked in the figure respectively. The values of ID and IG are within the above range. The intensity of the ID and IG peaks can be obtained by calculating the areas of the ID peak and IG peak marked in Tu 2.
[0065] The inventors have found that the ID1 / IG1 value of the surface layer and the ID2 / IG2 value of the matrix layer satisfy the above relationship, and the surface defect degree of the negative electrode active material layer is controlled within the above range. On the one hand, the surface defect degree of the negative electrode active material layer can be controlled, which is conducive to the formation of a dense and stable SEI film on the surface of the negative electrode active material layer. On the other hand, the negative electrode active material layer can have improved lithium ion insertion / extraction efficiency, thereby improving the first coulombic efficiency and cycle capacity retention rate of the secondary battery, and maintaining a balance between kinetic performance.
[0066] Therefore, by using the negative electrode active material of the present application, the secondary battery can simultaneously take into account a high first coulombic efficiency, a cycle performance retention rate and a kinetic performance.
[0067] In some embodiments of the present application, the thickness of the surface layer is 5 μm to 20 μm. Preferably, it is 5 μm, 8 μm, 10 μm, 15 μm, 18 μm, and 20 μm. By controlling the thickness of the surface layer within the above range, the surface defect degree of the surface layer having the above thickness can be better controlled, thereby controlling the formation of the SEI film and further improving the first coulombic efficiency and cycle capacity retention rate of the secondary battery.
[0068] In some embodiments of the present application, the thickness of the negative electrode active material layer is 30 μm to 160 μm, preferably 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, or 160 μm.
[0069] According to the embodiment of the present application, when the thickness of the negative electrode active material layer is within the above range, on the one hand, the negative electrode active material layer can achieve a suitable surface density, and on the other hand, the cycle capacity retention rate of the secondary battery and the balance of dynamic performance can be further improved. At the same time, if the thickness of the negative electrode active material layer is too small, for example, less than 30 μm, on the one hand, the thin negative electrode active material layer is easily infiltrated by the electrolyte, and the lithium ions are easier to be deintercalated. The surface layer and the matrix layer with different ID / IG values are set on the negative electrode active material layer, and the ratio of the ID / IG of the two is controlled, which has limited improvement on the performance of the secondary battery. On the other hand, if the negative electrode active material layer is too thin, the proportion of the negative electrode active material layer in the negative electrode sheet is reduced, thereby reducing the energy density of the secondary battery. If the negative electrode active material layer is too thick, for example, greater than 160 μm, it is difficult for the electrolyte to infiltrate the negative electrode active material in the middle, and the side reaction products caused by polarization are accumulated, and the cycle performance and dynamic performance of the secondary battery are deteriorated.
[0070] For example, along the longitudinal section direction of the negative electrode sheet, when the negative electrode active material layer is a single layer, the thickness may be 30 to 80 μm; when the negative electrode active material layer is a double layer, the thickness may be 60 to 160 μm.
[0071] In some embodiments of the present application, the maximum particle size of the negative electrode active material particles is ≤55 μm.
[0072] According to the embodiments of the present application, controlling the maximum particle size of the negative electrode active material particles is beneficial to the uniform mixing between the negative electrode active material particles and allows a close arrangement between the particles, thereby increasing the compaction density of the negative electrode active material layer and further increasing the energy density of the secondary battery; on the other hand, it can improve the effective capacity of the negative electrode active material particles and the kinetics of lithium ion insertion / extraction.
[0073] For example, the maximum particle size of the negative electrode active material particles can be determined by preparing a number of longitudinal slices of the negative electrode sheets and counting the negative electrode active material particles within the cross-sections of the longitudinal slices.
[0074] In some embodiments of the present application, the Dv50 of the negative electrode active material particles is 5 μm to 15 μm.
[0075] According to the embodiments of the present application, the Dv50 of the negative electrode active material particles is within the above range, preferably 8μm to 12μm, and more preferably 10μm to 11μm, which allows the particles to be arranged more closely, thereby increasing the compaction density of the negative electrode active material layer, and thus increasing the energy density of the secondary battery; on the other hand, it can be beneficial to balance the effective capacity of the negative electrode active material particles, the kinetics of lithium ion insertion / extraction, and the structural stability of the particles.
[0076] In some embodiments of the present application, the ratio of Dv90 / Dv10 of the negative electrode active material particles is 1.2 to 3.2.
[0077] According to the embodiments of the present application, the ratio of Dv90 / Dv10 of the negative electrode active material particles is within the above range, preferably 1.5 to 3.0, and more preferably 2.0 to 2.5, which can make the negative electrode active material particles have good particle size distribution characteristics, thereby allowing the negative electrode active material particles to be arranged more closely and better balancing the effective capacity of the negative electrode active material particles, the kinetics of lithium ion insertion / extraction, and the structural stability of the particles.
[0078] The particle size can be measured by instruments and methods known in the art. For example, the particle size distribution laser diffraction method according to GB / T 19077-2016 can be conveniently measured by a laser particle size analyzer, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.
[0079] In some embodiments of the present application, the negative electrode active material includes at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, and carbon-silicon composites.
[0080] In some embodiments of the present application, the negative electrode active material may be natural graphite, artificial graphite, mesophase microcarbon beads, amorphous carbon-coated graphite or a combination thereof, and may also include at least one of hard carbon, soft carbon, and carbon-silicon composites. According to the embodiments of the present application, a dense and stable SEI film may be formed on the surface of the negative electrode active material layer, effectively protecting the negative electrode active material from the corrosion of the electrolyte.
[0081] In some embodiments of the present application, the negative electrode active material includes at least one of natural graphite, artificial graphite, and mesophase microcarbon beads. The graphitization degree of the surface layer and the matrix layer can be measured respectively, and the relative surface defect degree of the surface layer and the matrix layer can be judged, thereby further ensuring the first coulombic efficiency, cycle capacity retention rate and kinetic performance of the secondary battery.
[0082] In some embodiments of the present application, the negative electrode plate further includes a primer layer disposed between the negative electrode current collector and the substrate layer, wherein the primer layer contains a conductive agent. Figure 3 Schematic diagram of an embodiment of a negative electrode sheet in another secondary battery of the present invention. The exemplary negative electrode sheet 10 includes a negative electrode current collector 11, a primer layer 12 located on both surfaces of the negative electrode current collector, and a negative electrode active material layer 13 located on the surface of the primer layer.
[0083] According to the embodiments of the present application, the primer layer provided between the negative electrode current collector and the substrate layer can improve the interface of the composite current collector, enhance the bonding force between the current collector and the active material, and ensure that the negative electrode active material layer is more firmly arranged on the surface of the current collector; in addition, it can well overcome the shortcomings of the poor conductivity of the composite current collector and the easy damage of the conductive layer in the composite current collector, by effectively repairing and constructing a conductive network between the current collector, the conductive primer layer and the active material; improving the electron transfer efficiency, reducing the resistance between the current collector and the negative electrode active material layer, thereby further improving the cycle performance of the secondary battery.
[0084] In some embodiments of the present application, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, carbon fibers and graphene.
[0085] According to this embodiment, the conductive agent is disposed in the bottom coating layer, which can further improve the conductivity of the bottom coating layer, reduce the resistance between the negative electrode active material layer and the current collector, thereby reducing electrode polarization, and can also improve the mechanical properties of the bottom coating layer, further improving the bonding strength between the current collector and the negative electrode active material layer.
[0086] In some embodiments of the present application, the thickness of the primer layer is 0.01 μm to 2 μm. Preferably, it is 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm. The thickness of the primer layer is within the above range, which is conducive to ensuring the total thickness of the primer layer and the negative electrode active material layer, and is conducive to controlling the thickness of the negative electrode active material layer within a suitable range, which is conducive to the cycle performance of the negative electrode sheet. It is conducive to ensuring the bonding strength between the current collector and the negative electrode active material layer without significantly sacrificing energy density.
[0087] In some embodiments of the present application, the negative electrode active material layer includes a first negative electrode active material layer and a second active material layer, the first negative electrode active material layer is arranged on at least one surface of the negative electrode current collector, and the second negative electrode active material layer is arranged on the surface of the first negative electrode active material layer facing away from the negative electrode current collector, and in the second negative electrode active material layer, the negative electrode active material comprises amorphous carbon-coated graphite.
[0088] In the above embodiments, the negative electrode active material layer includes a first negative electrode active material layer and a second negative electrode active material layer, and the first negative electrode active material layer is arranged on at least one surface of the negative electrode collector, and the second negative electrode active material layer is arranged on the surface of the first negative electrode active material layer away from the negative electrode collector. The arrangement of the double-layer active material layer can be beneficial to improving the kinetic performance of the secondary battery.
[0089] In the first negative electrode active material layer, the negative electrode active material contained therein may be at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, carbon-silicon composite, etc. By selecting the material within the above range, it is beneficial to improve the energy density of the secondary battery.
[0090] In the second negative electrode active material layer, the negative electrode active material contained therein may be at least one of natural graphite, artificial graphite, mesophase micro carbon beads, hard carbon, soft carbon, carbon-silicon composite, and amorphous carbon-coated graphite, which may further help improve the kinetic performance of the secondary battery. Other materials known in the art may also be used.
[0091] In some embodiments of the present application, the negative electrode active material layer also includes a binder, which can be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0092] In some embodiments of the present application, the negative electrode active material layer further includes a conductive agent, which can be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0093] In some embodiments of the present application, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0094] However, the present application is not limited to the above materials, and the negative electrode plate of the present application may also use other known materials that can be used as negative electrode active materials, conductive agents, binders and thickeners.
[0095] The negative electrode sheet in the present application can be prepared according to conventional methods in the art. For example, the negative electrode active material, the conductive agent, the binder and the thickener are dispersed in a solvent, and the solvent can be N-methylpyrrolidone (NMP) or deionized water to form a uniform negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector, and the negative electrode active material layer is obtained after drying and cold pressing to obtain the negative electrode sheet.
[0096] Secondary battery
[0097] An embodiment of the second aspect of the present application provides a secondary battery, comprising the negative electrode sheet according to the first aspect of the present application.
[0098] As described above, in the present application, a secondary battery includes any device that undergoes an electrochemical reaction to convert chemical energy into electrical energy. Secondary batteries include, for example, lithium-ion batteries, sodium-ion batteries, and other common secondary batteries in the art, a specific example of which is a lithium secondary battery, which may include a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0099] Specifically, according to an embodiment of the present application, a secondary battery includes an electrode assembly and an electrolyte. The electrode assembly includes a negative electrode sheet, a positive electrode sheet, and a separator disposed between the negative electrode sheet and the positive electrode sheet according to the first aspect of the present application.
[0100] The embodiments of the negative electrode sheet have been described and illustrated in detail above, and will not be repeated here. It can be understood that the secondary battery of the second aspect of the present application can achieve the beneficial effects of any of the above embodiments of the negative electrode sheet of the present application.
[0101] In an embodiment of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector and including a positive electrode active material.
[0102] It is understandable that the positive electrode sheet may be provided with a positive electrode active material layer on one surface of the positive electrode current collector, or may be provided with a positive electrode active material layer on both surfaces of the positive electrode current collector, and the embodiments of the present application do not specifically limit this.
[0103] The positive electrode current collector may be a metal foil or a porous metal plate, such as a foil or a porous plate of a metal such as aluminum, copper, nickel, titanium, iron, or an alloy thereof. In some embodiments of the present application, the positive electrode current collector is aluminum foil.
[0104] In some embodiments of the present application, the positive electrode active material can be selected from at least one of olivine structure materials such as lithium iron manganese phosphate, lithium iron phosphate, lithium manganese phosphate, ternary structure materials such as NCM811, NCM622, NCM523, NCM333, lithium cobalt oxide materials, lithium manganese oxide materials, and other metal oxides capable of deintercalating lithium.
[0105] In some embodiments of the present application, the positive electrode active material layer further includes a binder, which improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector. Exemplarily, the binder can be selected from at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.
[0106] In some embodiments of the present application, the positive electrode active material layer further includes a conductive agent, which is selected from at least one of a carbon-based material, a metal-based material, a conductive polymer, and a mixture thereof. Exemplarily, the carbon-based material is selected from carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotube, or any combination thereof. The metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. The conductive polymer is a polyphenylene derivative.
[0107] The positive electrode sheet in the present application can be prepared according to conventional methods in the art. For example, the active material, the conductive material and the binder are dispersed and mixed in N-methylpyrrolidone (NMP) to form a uniform positive electrode slurry, the positive electrode slurry is coated on the positive electrode current collector, and the positive electrode sheet is obtained after drying, cold pressing, cutting, slitting and re-drying.
[0108] In the embodiments of the present application, the isolation film may be polyethylene, polypropylene, polyvinylidene fluoride or a multi-layer composite film thereof.
[0109] In some embodiments of the present application, the isolation film is a single-layer isolation film or a multi-layer isolation film.
[0110] The embodiment of the present application has no particular limitation on the shape and thickness of the separator. The method for preparing the separator is a method for preparing a separator that can be used for a secondary battery and is well known in the art.
[0111] In the embodiment of the secondary battery of the present application, the electrolyte is a carrier for ion transmission, which can play a role in conducting ions between the positive electrode plate and the negative electrode plate, and is a guarantee for the secondary battery to obtain advantages such as good cycle performance.
[0112] In an embodiment of the present application, the electrolyte includes propylene carbonate (PC for short) and fluoroethylene carbonate (FEC for short). Propylene carbonate and fluoroethylene carbonate can act synergistically to form a stable SEI film on the surface of the negative electrode plate, thereby improving the high-temperature storage performance and high-temperature cycle performance of the secondary battery.
[0113] In the embodiments of the present application, under the premise of ensuring the high temperature cycle performance of the secondary battery, it is also necessary to improve the charge and discharge performance of the secondary battery. Therefore, the electrolyte also includes a lithium salt. The embodiments of the present application do not particularly limit the specific material of the lithium salt, which can be a lithium salt commonly used in the art. Exemplarily, the lithium salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), and lithium difluorooxalatoborate.
[0114] The electrolyte can be prepared according to conventional methods in the art. For example, an organic solvent, a lithium salt, and optional additives can be uniformly mixed to obtain an electrolyte, wherein the order of adding the materials is not particularly limited.
[0115] The secondary battery of the present application can be prepared by conventional methods in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet are stacked in order, the separator is placed between the positive electrode sheet and the negative electrode sheet, and then the electrode assembly is obtained by winding, the electrode assembly is placed in a shell, and then the electrolyte is injected, and the secondary battery can be obtained after vacuum packaging, static, formation, vacuum forming and other processes.
[0116] The housing may be a hard shell or a flexible shell. For example, the hard shell may be made of metal. The flexible shell may be made of metal plastic film, such as aluminum plastic film, steel plastic film, etc.
[0117] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 A secondary battery 5 of a square structure is shown as an example.
[0118] In some embodiments, reference Figure 5, the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0119] The secondary battery of the present application includes the negative electrode plate of the first aspect of the present application, and can also achieve the beneficial effects of each embodiment of the negative electrode plate according to the present application.
[0120] Electrical devices
[0121] On the other hand, the present application provides an electrical device, which includes the secondary battery provided by the present application. The secondary battery provided by the present application not only has good cycle capacity retention rate and balanced dynamics performance, but also enables the electrical device provided by the present application to have good cycle capacity retention rate and balanced dynamics performance.
[0122] The embodiments of the present application have no particular restrictions on the electrical device, and it can be applied to any electrical device known in the prior art. In some embodiments of the present application, the electrical device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery or a lithium-ion capacitor, etc.
[0123] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle or a plug-in hybrid electric vehicle.
[0124] The secondary battery electrical device of the present application comprises the negative electrode plate of the first aspect of the present application, and can also achieve the beneficial effects of each embodiment of the negative electrode plate of the present application.
[0125] Example
[0126] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0127] For the convenience of description, the following embodiments take a lithium-ion secondary battery as an example to describe the secondary battery and the manufacturing method thereof in detail.
[0128] Examples 1-4
[0129] (1) Cathode preparation
[0130] The positive electrode active material lithium cobalt oxide (LiCoO2), the conductive agent (acetylene black), and the binder polyvinylidene fluoride (abbreviated as PVDF) are dissolved in N-methylpyrrolidone (abbreviated as NMP) solvent in a weight ratio of about 97.6:1.2:1.2, and are fully stirred and mixed to obtain a positive electrode slurry; the positive electrode slurry is then coated on the positive electrode current collector aluminum foil; the aluminum foil is dried, cold pressed, cut into pieces, slit, and dried to obtain a positive electrode sheet.
[0131] (2) Negative electrode preparation
[0132] Preparation of negative electrode sheet (double-layer coating): Graphite with different particle sizes and no modification is selected as the negative electrode active material. The ID / IG value is adjusted by the different particle sizes of the negative electrode active material. Graphite with different particle sizes is dispersed in a deionized water solvent with a binder of styrene-butadiene rubber (SBR) and a thickener of sodium carboxymethyl cellulose (CMC) at a weight ratio of 97.7:1.2:1.1, and then fully stirred and mixed to obtain different negative electrode active slurries. Different negative electrode active slurries are sequentially coated on the negative electrode current collector copper foil. Double-layer coating is selected to control the surface defect degree of the negative electrode active material layer. Sample test the coating weight of the lower layer to reach the design standard value, and then continue to coat the upper layer. The coating weight value of the double layer is sampled and tested to reach the design standard value. Continue to perform double-sided coating according to this operation. Then the negative electrode sheet of the invention is obtained by rolling. The A value, B index and A / B value of the prepared negative electrode sheet are shown in Table 1.
[0133] (3) Preparation of isolation membrane
[0134] A polyethylene (PE) porous polymer film having a thickness of about 7 μm was used as the separator.
[0135] (4) Preparation of electrolyte
[0136] In an argon atmosphere glove box with a water content of <10ppm, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) (weight ratio of about 1:1:1) were mixed, and lithium salt LiPF6 was added and mixed evenly, wherein the concentration of LiPF6 was 1.15mol / L. Based on the total weight of the electrolyte, an appropriate amount of fluoroethylene carbonate (FEC) was added to the electrolyte.
[0137] (5) Preparation of lithium-ion batteries
[0138] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode and the negative electrode to play an isolating role, and then wound to obtain a bare cell; after welding the pole ear, the bare cell is placed in the outer packaging foil aluminum-plastic film, and after drying, the prepared electrolyte is injected into the dried bare cell, and the bare cell obtained by winding is placed in the outer packaging, and the electrolyte is injected and packaged, and a lithium-ion battery is obtained through the process of formation, degassing, trimming, etc. The lithium-ion batteries of the embodiments and comparative examples of the present application are prepared according to the above method.
[0139] Embodiment 5-9
[0140] The preparation method is similar to that of Example 1, except that the negative electrode material is prepared by selecting natural graphite ore, crushing / ball milling / flotation to obtain natural flake graphite, optimizing according to the morphology, section, hardness and particle size of flake graphite, and treating with a chelating agent and a pickling agent to obtain high-purity graphite. Then a series of surface modifications are performed on the high-purity graphite, mainly using powdered asphalt or other polymer substances to mix with high-purity graphite powder. The mixing equipment uses a powder mixing equipment with an isostatic pressing equipment, and the dosage is high-purity graphite: modifier 1:1~7:3. Then the mixture is graphitized at a treatment temperature of 2500~3300℃. After graphitization, the graphite is surface modified again, and the surface modifier used is a high-purity asphalt with a softening point of 100-350℃, and the dosage is graphite: modifier 80:20~99:1. Then the modified graphite is carbonized at a treatment temperature of 800-1500℃. That is, the ID / IG value of different negative electrode active materials is controlled by controlling the degree of surface coating of the negative electrode active material. The A value, B index and A / B value of the prepared negative electrode sheet are shown in Table 1. The particle size of the negative electrode active material particles of Example 6 is shown in Table 2.
[0141] Example 10
[0142] The preparation method is similar to that of Example 1, except for the preparation of the negative electrode sheet (single-layer coating): the negative electrode active material, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are dispersed in a deionized water solvent at a weight ratio of 97.7:1.2:1.1, stirred and mixed thoroughly, and then coated on the negative electrode current collector copper foil pre-coated with a conductive coating. The rolling process is carried out three times, and the difference in thickness between the second and third rolling is controlled between 5 and 20 μm, and the time interval is 12h to 24h. The surface defect of the negative electrode active material layer is controlled by the rolling process. The A value, B index and A / B value of the prepared negative electrode sheet are shown in Table 1.
[0143] Examples 11-23
[0144] The preparation method is the same as that of Example 6, except that the particle sizes of the negative electrode active material particles are different, as shown in Table 2.
[0145] Examples 24-33
[0146] The preparation method is the same as that of Example 16, except that the particle size of the negative electrode active material particles in the negative electrode plate, the thickness of the negative electrode active material layer, the thickness of the copper foil, the type and thickness of the primer are different, as shown in Table 3.
[0147] Comparative Example 1
[0148] The preparation method is similar to that of Example 6, and different proportions of surface modification materials are used in different base layers and surface layers, as shown in Table 1 below.
[0149] Comparative Example 2
[0150] The preparation method is the same as that of Example 6, except that the base layer and the surface layer use the same negative electrode active material, as shown in Table 1.
[0151] Test Section
[0152] (1) DC resistance test (DCR)
[0153] Charge the lithium-ion battery to 4.48V at a constant current of 1.5C, and then charge to 0.05C at a constant voltage; let it stand for 30 minutes; discharge at a current value of 0.1C for 10s (take a point once every 0.1s and record the corresponding voltage value U1), and discharge at a current value of 1C for 360s (take a point once every 0.1s and record the corresponding voltage value U2). Repeat the charge and discharge steps 5 times. "1C" is the current value that completely discharges the battery capacity within 1 hour, and "0.1C" is the current value that completely discharges the battery capacity within 110 hours.
[0154] The DCR is calculated according to the following formula: R = (U2-U1) / (1C-0.1C). The DCR of the present application is the value at 50% SOC (state of charge).
[0155] (2) 45℃ cycle test
[0156] Take the battery under test and place it at a test temperature of 45℃, let it rest for 5 minutes, charge the lithium-ion battery to 4.48V at a constant current of 1.5C, and then charge it to 0.05C at a constant voltage of 4.48V; let it rest for 5 minutes, and then discharge it to 3.0V at a constant current of 1.0C, and let it rest for 5 minutes. The capacity at this time is recorded as D0; repeat the above charge and discharge process 500 times, and record the last discharge capacity as D1; after cycling at 45℃, the capacity decay rate is D1 / D0.
[0157] (3) Volumetric energy density (VED)
[0158] Take the battery cell to be tested, charge it to 4.48V at 1.5C current under normal temperature conditions, and then charge it to 0.05C at a constant voltage of 4.48V; let it stand for 5 minutes, and then discharge it to 3.0V at a constant current of 0.025C, and let it stand for 5 minutes. The capacity at this time is recorded as D, in mAh. Then charge the battery cell to 4.0V at 1.0C, measure the length, width and thickness of the battery cell at this time, and calculate the volume V of the battery cell, in mm 3 , volume energy density calculation: VED = (D × 3.89 × 1000) / V, unit is Wh / L.
[0159] (4) Raman spectroscopy analysis
[0160] The negative electrode active materials in the embodiments and comparative examples were measured using a LabRAM HR Evolution laser micro-Raman spectrometer, wherein a solid laser with a wavelength of 523 nm was used as the light source, the beam diameter was 1.2 μm, and the power was 1 mW; the measurement mode was macro Raman; and a CCD detector was used.
[0161] The negative electrode active material powder was pressed into a tablet, and three points were randomly selected on the tablet for testing, and the average value of three groups of measured values was obtained.
[0162] Among them, the A value and the B value are only different in the position or area selection. Taking A as an example, the negative electrode sheet after full discharge (0% SOC) disassembly is selected, and the negative electrode sheet is processed by IB-09010 ion polishing instrument to obtain its cross section. Then transfer the cross-sectional sample to the objective stage of the HR Evolution Raman spectrometer for Raman analysis. Select the area of the surface layer and the matrix layer of the cross section for random frame selection and analysis of its ID / IG value. Test 5 parallel samples, and select 20 photos for each parallel sample. The average value of ID1 / IG1 of the surface layer is counted, recorded as A; the average value of ID2 / IG2 of the matrix layer is counted, recorded as B. The ID1 / IG1 value is the surface layer of A, where the value of A is 0.55 to 0.78; the value of B is 0.78 to 0.96.
[0163] According to the above preparation method, Examples 1 to 10 were prepared, and the value A of ID1 / IG1 of the surface layer of the negative electrode active material, the value B of ID2 / IG2 of the matrix layer, the ratio A / B and the effect of different graphite / modifier ratios of double-layer coating on the cycle performance and DCR performance of lithium-ion batteries are shown in Table 1.
[0164] Table 1 Preparation parameters and battery test data of negative electrode sheets corresponding to Examples 1-10 and Comparative Examples 1-2
[0165]
[0166]
[0167] In Table 1:
[0168] ID1 is the Raman shift of the negative electrode active material in the surface layer at 1328-1359 cm -1 IG1 is the peak intensity of the scattering peak at the surface layer where the Raman shift of the negative electrode active material is 1578-1585 cm -1 The peak intensity of the scattering peak at
[0169] ID2 is the Raman shift of the negative electrode active material in the matrix layer at 1328-1359 cm -1 The peak intensity of the scattering peak at IG2 is the peak intensity of the scattering peak at 1578-1585 cm-1. -1 The peak intensity of the scattering peak at .
[0170] As shown in Table 1, according to Example 1, Example 3 and Example 5, as the value A of ID1 / IG1 of the negative electrode active material surface layer of the negative electrode active material layer, the value B of ID2 / IG2 of the matrix layer, and the ratio A / B all increase, the cycle capacity retention rate shows a trend of gradually decreasing, and the DCR gradually decreases. This is because the increase in defects increases the electrochemical reaction sites of lithium ions, increases the channels for lithium insertion and extraction, and reduces polarization, which manifests as reduced impedance and improved kinetics. But at the same time, the increase in active sites also increases the consumption of active lithium required for film formation, thereby affecting the capacity retention rate after cycling.
[0171] In Examples 1-4 in Table 1, the upper and lower layers of the double-layer coating are coated with graphite particles of different particle sizes. Generally, the smaller the particle size, the more difficult it is to graphitize, and the more surface defects there are. That is, the ID / IG values of different negative electrode active layers are controlled by controlling different graphite particle sizes. It can be seen from Examples 1-4 that in order to control A / B within the range required by the present application, a balance between the cycle capacity retention rate and the DCR performance can be achieved.
[0172] In Table 1, Examples 5-9, the upper and lower layers of the double-layer coating use graphite with different coating ratios, and the ratio of graphite to modifier is adjusted to decrease. The value of A is also increasing, and the value of A / B is also increasing. This is because as the amount of modifier increases, the modifier is mainly a soft carbon structure after carbonization, so there are more defects, which leads to an increase in the defects of the surface layer of the negative electrode active material layer, that is, the ID / IG values of different negative electrode active material layers are adjusted by different degrees of modification of the graphite surface. For the kinetic performance of lithium-ion batteries, the main bottleneck is that the surface layer of the pole piece has a small porosity and a large impedance due to pressure, which causes a decrease in kinetics. Improving the defect degree of the surface layer can improve the kinetics of this area, thereby improving the overall kinetic performance.
[0173] In Example 10 of Table 1, different ID / IG values of the upper and lower layers can be obtained by controlling the thickness difference of the second and third rolling after single-layer coating.
[0174] According to the data of Comparative Example 1, the graphite used for the upper coating is not modified by a modifier. Combined with the polarized surface brought by high compaction, it is close to a closed-cell state. Therefore, the overall kinetic performance is poor, and due to the increase in polarization during the cycle, the SEI consumes more active lithium ions, which deteriorates the cycle capacity retention rate.
[0175] The data of Comparative Example 2 show that the cycle capacity retention rate and DCR of the negative electrode coated with the same active material on the upper and lower layers are significantly inferior to those of Examples 1-10.
[0176] It can be seen from the data in Table 1 that the negative electrode plate of the present application includes a negative electrode current collector; a negative electrode active material layer containing negative electrode active material particles disposed on at least one side of the negative electrode current collector, the negative electrode active material layer including: a surface layer with an ID1 / IG1 value of A, wherein the value of A is 0.55 to 0.78; a matrix layer with an ID2 / IG2 value of B, the matrix layer is located between the negative electrode current collector and the surface layer, wherein the value of B is 0.78 to 0.96; so that the negative electrode plate of the present application has a higher first coulomb efficiency and cycle life. In particular, when the Raman spectrum of the negative electrode active material layer satisfies: 0.60≤A / B<1.0, the cycle capacity retention rate of the negative electrode active material can be further improved. The use of the negative electrode plate of the present application can reduce DCR and improve the cycle capacity retention rate. At the same time, when 0.70≤A / B≤0.96, the cycle capacity retention rate and DCR can maintain a good balance due to the more stable SEI film formation; when 0.75≤A / B≤0.85, the cycle capacity retention rate and DCR of the battery can achieve the best match.
[0177] Furthermore, Examples 11 to 23 were prepared according to the above preparation method. The effects of Dv50, Dv90 / Dv10 of the negative electrode active material particles and the maximum particle diameter on the longitudinal section on the cycle capacity retention rate and direct current resistance (DCR) of the lithium-ion battery are shown in Table 2.
[0178] The above particle size measurement method refers to GB / T 19077-2016 particle size distribution laser diffraction method, and is conveniently measured using a laser particle size analyzer, such as the Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK.
[0179] Table 2 Particle sizes of negative electrode active material particles and battery test data corresponding to Examples 11-23.
[0180]
[0181] As shown in Table 2, based on Example 6 in Table 1, the effects of graphite type and particle size of negative electrode active material on lithium-ion battery cycling and DCR were further explored.
[0182] According to Examples 11-21, as Dv50 gradually increases, the maximum diameter of the particles also increases. Through particle size screening and grading, the value of Dv90 / Dv10 is further reduced. At this time, the cycle capacity retention rate gradually increases, while the DC resistance DCR gradually increases. This is because in the longitudinal section direction, the increase in particle size Dv50 will lead to a decrease in the pores of the pole piece, and the consumption of active lithium ions acting on the SEI membrane will decrease, resulting in an increase in the cycle capacity retention rate. The increase in particle size leads to an increase in the diffusion path of lithium ions, so its DC resistance will increase and the kinetics will deteriorate.
[0183] According to Example 22, when Dv50 is reduced to 4.5 μm, the maximum diameter of the particles is reduced to 20 μm. At this time, the particle size is too small. During the crushing process, the surface of the particles will increase due to the fresh surface caused by crushing, and new defects may appear. Therefore, compared with Examples 16-21, the cycle retention rate is significantly reduced, and due to the accumulation of by-products, the DCR also increases.
[0184] According to Example 23, when Dv50 increases to 20um, the maximum diameter of the particles increases to 58um. At this time, the particle size is too large, and the transmission path of lithium ions inside the particles will become longer. Therefore, during the cycle, the electrochemical polarization will increase, which is manifested as an increase in DCR impedance. At the same time, the particle size is too large, and it is easy to scratch the current collector during the preparation process, causing safety problems.
[0185] Furthermore, Examples 24-33 were prepared according to the above preparation method, and the thickness of the negative electrode active material layer, the thickness of the copper foil, the type and thickness of the primer coating had an effect on the volume energy density VED, the cycle capacity retention rate and the DC impedance of the lithium-ion battery, as shown in Table 3.
[0186] Table 3 The thickness of the negative electrode active material layer, copper foil thickness, primer type and thickness, and battery test data corresponding to Examples 23-32.
[0187]
[0188] As shown in Table 3, based on Example 16 in Table 2, the thickness of the negative electrode active material layer is further explored in terms of its effect on the volume energy density VED, cycle capacity retention rate and DCR.
[0189] According to Examples 24-29, as the thickness of the single layer of the lithium-ion negative electrode active material layer gradually increases, the thickness of the copper foil gradually decreases, the thickness of the primer layer gradually decreases, the volume energy density of the lithium-ion battery gradually increases, the cycle performance gradually decreases, and the DCR gradually increases. This is because as the thickness of the negative electrode active material layer increases, the proportion of active material per unit volume will increase, and a higher capacity can be exerted in the same volume, and the thickness of the copper foil and the thickness of the primer layer gradually decrease, which is also conducive to the volume energy density. The reduction in cycle performance is due to the fact that as the thickness of the negative electrode active material layer increases, the wettability of the electrolyte gradually deteriorates, and the side reaction products caused by its polarization accumulate, which manifests as a double deterioration of the cycle and kinetics.
[0190] As shown in Examples 30-32, using different nano primers will result in different energy densities, cycle performances, and kinetic performances, which are significantly related to the characteristics of the nano primer itself and the amount added.
[0191] According to Example 33, when the thickness of the negative electrode active material layer is reduced to 25 μm, the thickness of the copper foil is reduced to 3 μm, and the thickness of the primer is reduced to 3 μm, the processing performance is greatly affected, the appearance of the negative electrode active material layer will have more bumps, and after being made into a battery cell, its volume energy density is low, and the cycle and kinetic performance will also be poor. Therefore, it is necessary to use a suitable thickness of the negative electrode active material layer, and use a suitable primer and copper foil thickness to achieve better electrochemical performance.
[0192] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A negative electrode sheet, comprising: Anode current collector; A negative electrode active material layer containing negative electrode active material particles is disposed on at least one side of the negative electrode current collector, and the negative electrode active material layer includes: The ID1 / IG1 value is A on the surface layer, wherein 0.55≤A≤0.78, and ID1 is the Raman shift of the Raman spectrum of the negative electrode active material in the surface layer at 1328-1359 cm -1 IG1 is the peak intensity of the scattering peak at the Raman shift of 1578-1585 cm -1 The peak intensity of the scattering peak at ; The ID2 / IG2 value is B for the matrix layer, the matrix layer is located between the negative electrode current collector and the surface layer, wherein 0.78≤B≤0.96, ID2 is the Raman spectrum of the negative electrode active material in the matrix layer at a Raman shift of 1328 to 1359 cm -1 IG2 is the peak intensity of the scattering peak at the Raman shift of 1578-1585 cm -1 The peak intensity of the scattering peak at ; The negative electrode active material layer satisfies: 0.60≤A / B<1.0; The negative electrode plate meets at least one of the following conditions: (1) The maximum particle size of the negative electrode active material particles is ≤55 μm; (2) The Dv50 of the negative electrode active material particles is 5 μm to 15 μm; (3) The ratio Dv90 / Dv10 of the negative electrode active material particles is 1.2 to 3.
2.
2. The negative electrode sheet according to claim 1, characterized in that: 0.70≤A / B≤0.
96.
3. The negative electrode sheet according to claim 2, characterized in that: 0.75≤A / B≤0.
85.
4. The negative electrode sheet according to claim 1, characterized in that: The thickness of the surface layer is 5 μm to 20 μm.
5. The negative electrode sheet according to claim 1, characterized in that: The thickness of the negative electrode active material layer is 30 μm to 160 μm.
6. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material comprises at least one of natural graphite, artificial graphite, mesophase micro carbon beads, hard carbon, soft carbon, and carbon-silicon composite.
7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The negative electrode sheet further includes a primer layer disposed between the negative electrode current collector and the base layer, wherein the primer layer contains a conductive agent.
8. The negative electrode sheet according to claim 7, characterized in that: The conductive agent includes at least one of conductive carbon black, carbon nanotubes, carbon fibers and graphene.
9. The negative electrode sheet according to claim 7, characterized in that: The primer layer has a thickness of 0.01 μm to 2 μm. 10 . A secondary battery comprising the negative electrode sheet according to claim 1 .
11. An electrical device comprising the secondary battery according to claim 10.
Citation Information
Patent Citations
Electrochemical device and electronic equipment
CN113097433A
Negative pole piece, electrochemical device and electronic equipment
CN114824165A